1988
DOI: 10.1111/j.1525-1446.1988.tb00559.x
|View full text |Cite
|
Sign up to set email alerts
|

Toward Healthy Aging: A Theory for Community Health Nursing

Abstract: In this research project we explored beliefs about healthy aging in an Appalachian community. A major goal was to develop theory for community health nursing interventions that promote and maintain health during the aging process. A convenience sample of 105 community informants responded to an open-ended interview schedule that elicited beliefs and values of health and aging. The data were analyzed for the purpose of producing grounded theory; a major category that emerged portrayed the aging process as a col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 6 publications
2
12
0
1
Order By: Relevance
“…revealed that the subjects generally understood and practiced commonly accepted modes for maintaining health, such as monitoring diet and watching weight, exercising regularly, obtaining adequate sleep and rest, and having regular health checkups. These findings are similar to those reported by Boyle and Counts (1988) in an ethnographic study in Appalachia.…”
Section: Discussionsupporting
confidence: 94%
“…revealed that the subjects generally understood and practiced commonly accepted modes for maintaining health, such as monitoring diet and watching weight, exercising regularly, obtaining adequate sleep and rest, and having regular health checkups. These findings are similar to those reported by Boyle and Counts (1988) in an ethnographic study in Appalachia.…”
Section: Discussionsupporting
confidence: 94%
“…Kolanowski and Gunter's (1985) qualitative study with older women resulted in patterns that were very similar to those reported in the present study. Boyle and Counts (1988) found patterns similar to Attending to Health Behaviors and Staying Active in their study of Appalachian elders, but did not find maintaining relationships to be central to health in that context.…”
Section: Discussionmentioning
confidence: 82%
“…Community health nursing emphasizes health‐oriented care for people. The major goal of community nurses is “to increase health rather than to decrease illness” ( Boyle & Counts, 1988, p. 46). For older adults, health promotion must be emphasized as the basis of everyday life ( Alford & Futrell, 1992).…”
Section: Introductionmentioning
confidence: 99%